(untitled) (Philadelphia, PN, 1999)
Univ. of Pennsylvania, Philadelphia. Synopsis and atlas of the author's Brandon/Hill title: Lever's Histopathology of the Skin, 8th ed, c1997. For dermatology and pathology students and practitioners. Includes color slides and photographs.
Keywords: Skin; Histopathology,Atlases